Respuesta :

1. 1/3 u when u = (1,-3)
replace the u with the given values:
1/3(1) and 1/3(-3)
1/3(1) = 1/3
1/3(-3) = -1
answer is (1/3, -1)

2. u = (1,3) v = (2,6)
u + v =  add the first 2 numbers and then the 2nd 2 numbers:
(1+2) and (3+6) = (3,9)

3. v = (2,6) and u = (1,3)
u-v = subtract the first 2 numbers, then the second 2 numbers:
(1 -2) and (3-6) =  (-1,-3)

4. u = (1,3) v = (2,6)
2v +u = multiply both v numbers by 2 than add to the u values:

2v = (2*2, 2*6) = (4,12)

add to u = (4+1, 3+12) = (5,15)